Meniscal stress biomechanics in Tai Chi’s Brush knee and Twist Step for elderly - Chen, Fengzhen; Chen, Huan; Chen, Sheng; Lin, Jiaqiu (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveThis study investigates the biomechanical effects of long-term Tai Chi practice on the knee meniscus through biomechanical experimentation and finite element simulation, focusing on practitioners performing Knee Brushing and Twisting Step. The findings aim to establish scientific guidelines for optimizing exercise protocols in middle-aged and elderly populations.MethodsTwenty male middle-aged and elderly practitioners were recruited, divided into a Beginner Group (BG: n = 10), and an Experienced Group (EG: n = 10). Kinematic and kinetic data during Knee performance of Brushing and Twisting Step were collected using synchronized three-dimensional infrared motion capture and force platforms. A finite element model was developed and validated based on knee CT and MRI imaging data from a representative participant with average anthropometric measurements. The acquired kinematic and kinetic data were applied as boundary conditions and loading inputs in finite element analysis software to simulate the knee joint contact stress distribution during movement execution.Results(1) The Experienced Group demonstrated significantly greater knee flexion angles compared to the Beginner Group across all movement phases (P < 0.01), while exhibiting significantly lower varus-valgus and internal-external rotation angles (P < 0.01). (2) The Experienced Group exhibited phase-specific peak contact stress distribution: predominantly on the lateral meniscus during (left) double-support, (left) swing, (left) single-support, and terminal (right) swing phases, shifting to the medial meniscus during (right) double-support, initial (right) swing, and (right) single-support phases. In contrast, the Beginner Group demonstrated consistent lateral meniscus stress concentration across all phases except during the (right) swing phase.ConclusionLong-term practice of Tai Chi optimizes the distribution of stress across the knee joints, effectively reducing localized stress concentrations and the associated risks of meniscal injuries. For novice practitioners, it is crucial to emphasize precision in movement and adherence to technical standards to prevent knee injuries that may arise from improper biomechanical loading patterns.